THE IMPORTANCE OF COMPLEMENTARY FEEDING IN THE PHYSICAL DEVELOPMENT OF CHILDREN - Nosir Abdullayev (Modern American Journals, 2025)
Complementary feeding plays a crucial role in the healthy physical development of infants and young children. This article examines the timing, type, and nutritional quality of complementary foods and their impact on the growth indicators such as weight, height, and body mass index (BMI) in children aged 6 to 24 months. The study emphasizes the significance of introducing appropriate complementary foods alongside continued breastfeeding to support optimal physical growth and development.
Keywords: Complementary feeding, child growth, physical development, infant nutrition, weaning, anthropometric indicators.